Math, asked by bhargavkumar1, 1 year ago

solve this by rationalise the number.

Attachments:

Answers

Answered by ShuchiRecites
1
Hello Mate!

x =  \frac{1}{3 -  \sqrt{8} }  \\  \frac{1}{3 -  \sqrt{8} }  \times  \frac{3 +  \sqrt{8} }{3 +  \sqrt{8} }  \\  \frac{3 +  \sqrt{8} }{9 - 8}  = 3 +  \sqrt{8}  \\  {x}^{3}  =  {(3 +  \sqrt{8} )}^{3}  \\  = 27 + 8 \sqrt{8}  + 3 \times  {3}^{2}  \times  \sqrt{8}  + 3 \times 3 \times  { \sqrt{8} }^{2}  \\  = 27 + 8 \sqrt{8}  + 27 \sqrt{8}  + 72 \\ =  99 + 35 \sqrt{8}  \\ 2 {x}^{2}  = 2 {(3 +  \sqrt{8}) }^{2}  \\ 2(9 + 8 + 6 \sqrt{8} ) = 34 + 12 \sqrt{8}  \\ 7x = 7(3 +  \sqrt{8} ) = 21 + 7 \sqrt{8}  \\ 99 + 35 \sqrt{8}  - 34 - 12 \sqrt{8}  - 21 - 7 \sqrt{8}  + 5 \\  = 49+ 16 \sqrt{8}  \\  = 49 + 32 \sqrt{2}

Hope it helps☺!
Similar questions